Limited Liability and the Risk-Incentive Relationship - Jörg Budde; Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
Several empirical findings have challenged the traditional view on the trade-off between risk and incentives. By combining risk aversion and limited liability in a standard principal-agent model the empiri- cal puzzle on the positive relationship between risk and incentives can be explained. Increasing risk leads to a less informative performance signal. Under limited liability; the principal may optimally react by in- creasing the weight on the signal and; hence; choosing higher-powered incentives.
Keywords: D82; D86; 330; moral hazard; limited liability; risk-incentive relationship; Moral Hazard; Beschränkte Haftung; Leistungsanreiz; Risikoaversion; Agency Theory; Theorie